Analysis of Promotion Strategy on PRUCinta Syariah Life Insurance Products Through Social Media (Study at PT. Prudential PRUFure Team BJ8 in Banjarmasin) - Nikmah Nikmah; Faridah Faridah; Ahda Fithriani; Faqih El Wafa (AHKAM, 2025)
This research explores the promotional strategy for the PruCinta Sharia life insurance product through social media, with a focus on the implementation of Islamic principles in marketing practices at PT. Prudential Prufure Team BJ8 in Banjarmasin. The study is motivated by the central role of ethical strategy in Sharia-compliant insurance, emphasizing the prohibition of dishonest practices such as fraud, deceit, and exploitation. Employing a qualitative descriptive approach, data were collected through interviews with nine informants and analyzed using data reduction, data presentation, and conclusion drawing techniques. The findings indicate that the promotional strategy is carefully designed and centers on leveraging social media to maximize outreach and engagement. Instagram emerged as the most effective platform due to its visual appeal and ability to connect directly with potential clients. The strategy aligns with Islamic ethical standards, emphasizing transparency, honesty, and fairness in the communication of product benefits. The use of social media not only enhances visibility but also fosters trust and relatability among target audiences. The study concludes that ethically grounded and strategically executed social media promotion is key to advancing the reach and credibility of Sharia life insurance products like PruCinta.